Impact of Spatial Evolution of Cropland Pattern on Cropland Suitability in Black Soil Region of Northeast China, 1990–2020 - Long Kang; Kening Wu (Agronomy)
Agricultural land resources are essential for food production, and thus it is vital to examine the spatiotemporal changes in these resources and their impacts on land suitability to optimize resource allocation. In this study, we investigated the spatial evolution of cropland resources through land use change analysis by utilizing four periods of land use data from 1990 to 2020 in the black soil region of northeast China (BSRNC). Employing niche theory, we developed a cultivability evaluation model tailored to the BSRNC, which was used to assess the impact of the spatial changes in cropland patterns over the past 30 years on land suitability. Our key findings are as follows: (1) Cropland resources have generally tended to expand in the BSRNC, with an increase of 7.16 × 103 km2 in the cultivated area and a northeastward shift in the cropland center by 52.94 km, indicating significant changes in the spatial configuration of the land. (2) The region’s cultivable land resources were substantial, covering 694.06 × 103 km2, or 55.78% of the total area, with notable spatial variability, influenced by the regional climate and topography. (3) The land cultivability has slightly improved, as shown by a 0.10 increase in the cultivability index, but a significant declining trend in the cultivability of cropland was observed after 2000. Our findings provide valuable insights to help accurately assess land productivity in the BSRNC and facilitate the sustainable use and conservation of black soil.